A Merlion at the Edge of an Afrasian Sea: Singapore’s Strategic Involvement in the Indian Ocean - Chew, Emrys (2016)
The temporal-spatial dimensions of the Indian Ocean have been variously explored and described, the historical narrative adapted according to the interests of its invaders and inhabitants alike. Yet against the sometimes overlapping claims of Pax Indica, Pax Sinica, Pax Islamica, Pax Britannica and Pax Americana, the ocean was never a ‘lake’ controlled or owned exclusively by any single power based outside or inside its geographical boundaries. For millennia, it was a cosmopolitan arena animated by encounters between East and West, where Asians, Africans and Caucasians participated together in a sophisticated structure of commerce and politics shaped by the cycle of monsoons. The Indian Ocean arena, extending to the South China Sea, had been central in international history well before the rise of the Atlantic and the Pacific. The Indian Ocean’s centrality in international geopolitics is again becoming apparent, with the end of the Western colonial empires and the emergence of independent nation-states throughout Africa and Asia; and, more recently, the conclusion of the Cold War, the concurrent rise of India and China, the growing concerns over energy supplies, and the continuation of post-9/11 asymmetric conflicts. But what has all this meant for Singapore, a ‘global’ port-city located at the eastern fringe of that ‘globalizing’ arena? To what extent are the fortunes of Singapore bound up with the security and destiny of the Indian Ocean? From a geo-economic viewpoint, the stability of the Indian Ocean arena remains vital to Singapore, which, overlooking a key choke point and sea-lanes between two oceans, has long relied upon seaborne commerce for its viability. From a geo-strategic viewpoint, Singapore continues to espouse a multiplicity of policies and partnerships that it perceives would better guarantee its survival and success in the region. This paper examines the evolutionary dynamics of Singapore’s strategic involvement in the Indian Ocean.